Exosomal miR-223-3p from bone marrow mesenchymal stem cells targets HDAC2 to downregulate STAT3 phosphorylation to alleviate HBx-induced ferroptosis in podocytes - Chen, Yueqi; Yang, Xiaoqian; Feng, Moxuan; Yu, Yani; Hu, Yongzheng; Jiang, Wei (Frontiers in Pharmacology, 2024)
Background Hepatitis B virus associated-glomerulonephritis (HBV-GN) is one of the major secondary renal diseases in China, and microRNAs(miRNAs) in bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exo) can attenuate HBV-X protein (HBx)-induced ferroptosis in renal podocytes, but the exact mechanism remains unclear.This study aimed to investigate the protective mechanism of miR-223-3p in BMSC-Exo in HBx-induced ferroptosis in podocytes.The study employed human renal podocyte cells (HPCs), bone marrow-derived mesenchymal stem cells (BMSCs), as well as kidney tissue from C57BL/6 mice and HBx transgenic mice. Initially, the correlation between STAT3 phosphorylation and ferroptosis was authenticated through the administration of signal transducer and activator of transcription 3 (STAT3) phosphorylation inhibitors in both in vivo and in vitro settings. Furthermore, the effect of HDAC2 overexpression on STAT3 phosphorylation was examined. Subsequently, the association between BMSC-Exo carrying miR-223-3p, HDAC2, and the phosphorylation of STAT3 in HPCs ferroptosis and injury induced by HBx was assessed. The interaction between miR-223-3p and HDAC2 was confirmed via RIP assay. Various techniques such as cell counting kit-8 assay, western blot, RT-qPCR, immunofluorescence, flow cytometry, lipid peroxidation assay Kit, Iron Assay kit, transmission electron microscopy, and HE staining were employed to visualize the extent of HBX-induced podocyte injury and ferroptosis in both in vivo and in vitro. Results The attenuation of podocyte ferroptosis can be achieved by inhibiting the phosphorylation of STAT3 in podocytes induced by HBx. Conversely, the upregulation of HDAC2 can enhance STAT3 phosphorylation, thereby promoting podocyte ferroptosis. MiR-223-3p was capable of directly exerting negative regulation on HDAC2 expression. BMSC-Exo carrying miR-223-3p can effectively suppress the expression of HDAC2, ultimately leading to reduced HBX-induced ferroptosis in podocytes by targeting HDAC2 with miR-223-3p and downregulating STAT3 phosphorylation.Conclusion This study evidences the potential of BMSC-Exo mediated delivery of miR-223-3p in mitigating HBX-induced ferroptosis in podocytes, thereby offering a novel therapeutic target and approach for treating HBV-GN and alleviating renal injury.